1996
DOI: 10.1002/(sici)1097-4652(199609)168:3<499::aid-jcp2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the insulin-like growth factor-I receptor inhibits tumor necrosis factor-induced cell death

Abstract: The effect of insulin-like growth factor (IGF) on tumor necrosis factor (TNF)-induced cell killing was determined for mouse BALB/c3T3 fibroblasts in vitro. Cells maintained in 0.5% fetal bovine serum (FBS) were killed by TNF within 6 h in a concentration-dependent manner, an effect that was prevented by IGF-I. TNF-induced cytotoxicity of 3T3 cells that overexpress the human IGF-I receptor (p6 cells) was prevented by IGF-I alone in the absence of serum. TNF-induced cell death was associated with the morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 56 publications
(38 reference statements)
4
48
0
Order By: Relevance
“…Recent studies of cellular apoptotic sensitivity suggest that growth factors which transduce their proliferative signals through activation of a tyrosine kinase cascade can modulate cellular sensitivity to a variety of apoptotic signals (Wu et al, 1996;Gardner and Johnson, 1996;Tilly et al, 1992;Garcia-Lloret, 1996). These studies parallel those previously described for the protective e ects of speci®c growth factors which activate receptor tyrosine kinases and inhibit TNF-induced apoptosis (Sugarman et al, 1987).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Recent studies of cellular apoptotic sensitivity suggest that growth factors which transduce their proliferative signals through activation of a tyrosine kinase cascade can modulate cellular sensitivity to a variety of apoptotic signals (Wu et al, 1996;Gardner and Johnson, 1996;Tilly et al, 1992;Garcia-Lloret, 1996). These studies parallel those previously described for the protective e ects of speci®c growth factors which activate receptor tyrosine kinases and inhibit TNF-induced apoptosis (Sugarman et al, 1987).…”
Section: Introductionmentioning
confidence: 55%
“…Several reports have demonstrated that growth factors which activate receptor tyrosine kinases are able to delay or prevent apoptosis driven by TNF and other stimuli (Gardner and Johnson, 1996;Tilly et al, 1992;Garcia-Lloret et al, 1996;Sugarman et al, 1987;Shephard and Lewis, 1988;Nishikawa et al, 1994;Aggarwal et al, 1994;Wu et al, 1995) whereas ampli®ed expression of tyrosine kinases may constitutively activate survival signals and reduce the apoptotic actions of TNF (Wu et al, 1996;Gardner and Johnson, 1996;Garcia-Lloret et al, 1996;Sugarman et al, 1987;Hudziak et al, 1988;Lewis, 1988, Nishikawa et al, 1994;Aggarwal et al, 1994). In earlier studies we presented evidence of a role for overexpression of EGFr in loss of TNF sensitivity in two squamous carcinoma cell lines and subsequently demonstrated that inhibition of EGFr enzymatic activity with tyrphostin increased sensitivity to TNF (Nishikawa et al, 1994;Donato et al, 1993;Perez and Donato, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-IR is overexpressed by a variety of human malignancies, including pancreatic adenocarcinoma (Bergmann et al, 1995;Ouban et al, 2003). Numerous studies have demonstrated that both overexpression and overactivity of IGF-IR are associated with malignant transformation, increased tumor aggressiveness and protection from apoptosis (Kaleko et al, 1990;Macaulay, 1992;Sell et al, 1995;Wu et al, 1996;Prisco et al, 1997). Circulating IGF-I levels modulate gastrointestinal tumor growth and liver metastasis in vivo (Wu et al, 2002), and IGF-I stimulates cellular invasiveness and metastasis in human tumors including pancreatic adenocarcinoma (Stracke et al, 1989;Long et al, 1998a b;Tanno et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…22 Overexpression of IGF-IR protects cells from UV irradiation-, cytokine-and gamma radiation-induced apoptosis. [22][23][24] Recent studies suggested that the molecular alteration that results in enhanced activation of IGF-IR pathways could represent one mechanism of resistance to trastuzumab, a humanized antibody against HER2/neu, used in breast cancer therapy. 25,26 Strategies using either murine monoclonal antibodies, [27][28][29][30] dominant-negatives mutants 31 or antisense oligonucleotides 32 directed against IGF-IR mRNA have been reported to inhibit in vitro and/or in vivo tumor proliferation.…”
mentioning
confidence: 99%